(untitled) (The International Journal for Scientific Research, 2026)
This study aimed to identify the impact of Implementing Total Quality Management (TQM) on institutional performance in private hospitals In Riyadh. Specifically, the study sought to measure the level of implementation of TQM dimensions (top management commitment and support, patient focus, process management, continuous Improvement, employee participation and empowerment) and the level of Institutional performance (financial performance, patient satisfaction, internal processes, learning and growth) In private hospitals In Riyadh, and to test the relationship between these two variables the study adopted a descriptive analytical approach, and data were collected using an electronic questionnaire distributed to a stratified random sample of 271 employees working in private hospitals in Riyadh, with 254 valid questionnaires retrieved for statistical analysis, representing a response rate of 93.7%. Additionally, 14 semi-structured personal interviews were conducted with officials and experts in the field of quality and management. Data were analyzed using the Statistical Package for Social Sciences (SPSS) the study reached several Important findings: The level of implementation of TQM dimensions in private hospitals in Riyadh was high, with an overall mean of (3.98), and the level of institutional performance was also high, with an overall mean of (3.94). The results showed a positive, strong, and statistically significant correlation between TQM dimensions and institutional performance, with a correlation coefficient of (0.795). Multiple regression analysis results showed a statistically significant impact of TQM dimensions on Institutional performance, with a coefficient of determination (R²) value of (0.712), meaning that TQM dimensions explain 71.2% of the variance in institutional performance. The results also indicated that "process management" had the greatest impact on institutional performance, followed by "top management commitment and support," then "patient focus," followed by "continuous improvement," and finally "employee participation and empowerment." The results showed no statistically significant differences in respondents’ responses regarding the level of TQM dimensions implementation and the level of Institutional performance attributed to variables (gender, age, educational qualification), while differences were found attributed to variables (job title, years of experience). In light of these findings, the study presented several recommendations, the most important of which are: the need to Increase top management support and commitment to implementing TQM, enhance employee participation and empowerment, develop an effective system of incentives and rewards to encourage employees to participate In quality improvement, Improve patient satisfaction measurement systems and procedures, develop process management, and enhance continuous improvement.